2021
DOI: 10.1186/s13045-021-01106-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of frontline treatment approach on outcomes of myeloid blast phase CML

Abstract: Background The natural course of untreated chronic myeloid leukemia (CML) is progression to an aggressive blast phase. Even in the current era of BCR-ABL1 tyrosine kinase inhibitors (TKIs), the outcomes of blast phase CML remain poor with no consensus frontline treatment approach. Methods We retrospectively analyzed the response rates and survival outcomes of 104 consecutive patients with myeloid blast phase CML (CML-MBP) treated from 2000 to 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The use of hypomethylating agents such as decitabine might improve the treatment of CML as previously demonstrated for myelodysplastic diseases such as chronic myelomonocytic leukemia (CMML) [ 30 ]. Retrospective analysis has shown that combined front-line treatment with a second- or third-generation TKI and a hypomethylating agent or intensive chemotherapy leads to improved response rates and outcome in myeloid blastic crisis followed by allogeneic stem cell transplantation [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of hypomethylating agents such as decitabine might improve the treatment of CML as previously demonstrated for myelodysplastic diseases such as chronic myelomonocytic leukemia (CMML) [ 30 ]. Retrospective analysis has shown that combined front-line treatment with a second- or third-generation TKI and a hypomethylating agent or intensive chemotherapy leads to improved response rates and outcome in myeloid blastic crisis followed by allogeneic stem cell transplantation [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…A novel strategy is required for the optimal selection of TKI therapies during long-term therapy (85). After achieving treatment-free remission, monitoring of BCR::ABL1 transcript levels is still requiredto detect loss of MMR early and restart TKI therapy even with novel therapies (86)(87)(88)(89)(90)(91). Eltrombopag can be considered in managing TKI-related thrombocytopenia during TKI therapy (92).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Long-term survival rates were similar between IC + TKI and HMA + TKI, with a long-term survival rate of around 30% and improved outcomes for patients who were able to undergo ASCT (allogeneic stem cell transplant). However, while being less intensive than an IC method, the combination of HMA and second/third generation TKI is extremely successful (Saxena et al, 2021). As a result of their poor prognosis, patients with CML-BP require novel treatment options (Jain et al, 2017).…”
Section: Concomitant Use Of Tki and Ic/hma In Myeloid Bp-cml Patientsmentioning
confidence: 99%